The Main Determinants of Innovation and Export Complexity - Shahmamedova, Nazrin (ADA University, 2020)
Economic growth and development require greater access to the international market while developing countries face difficulties in terms of improving their indicators of economic complexity and innovation which is the necessity for reaching global markets. The purpose of this study was to investigate the factors which influence the economic complexity and innovation and the role of gender diversity in the relationship between ease of doing business and innovation. For testing the hypotheses, the secondary data provided by the global organization, the sample of 63 countries, and multiple regression analyses were used. The results confirm that ease of doing business positively affects innovation and the complexity of exports of a particular country. In addition, innovation also has a positive significant effect on the complexity of exports. Findings also revealed that gender diversity moderates the relationship between ease of doing business and innovation. In other words, ease of doing business has a greater influence on innovation when the workforce of the country is more balanced in the number of males and females. This study contributes to a better understanding of the factors that explain how human capital can be translated into greater county-level achievement. Thus, promoting entrepreneurship and gender equality must be in the center of governmental policies to be able to achieve long term sustainable growth and development.
Keywords: Business; Exports -- Azerbaijan.; Export marketing -- Azerbaijan.